Multinationals and indigenous employment: an "Irish disease"? - Barry, Frank; Hannan, Aoife (Economic & Social Studies, 1995)
In trade studies, Ireland emerges as having a revealed comparative disadvantage in labour-intensive industries. Can the country's unusual industrial structure contribute to our understanding of its high unemployment? The Dutch-disease models we explore suggest that the inflow of multinationals would have stimulated employment when the exchange rate was linked to sterling, but could have had less benevolent consequences when the exchange rate became more flexible. We also discuss a number of alternative hypotheses on the relationship between multinational and aggregate employment.
Keywords: Multinational companies; Employment; Ireland; Job market